Healthcare Experience Satisfaction among Generation Z: Quality, Procedures, and Information Access - Saptarani, Yanna Dwi; Irviana, Fitriyati (Asosiasi Dosen Muda Indonesia, 2026)
User satisfaction is a critical indicator for evaluating the performance of healthcare facilities, particularly as public expectations increasingly emphasize service quality, clear procedures, and accessible information. However, evidence on how these factors jointly shape satisfaction in healthcare settings remains important to clarify. Objective: This study aims to analyze the influence of service quality, service delivery procedures, and ease of access to information on satisfaction with the experience of using healthcare facilities. Methods: A quantitative survey approach was employed. Data were collected through questionnaires from 60 respondents who had previously used healthcare facilities. The data were analyzed using descriptive statistics and multiple linear regression to examine both partial and simultaneous effects among variables. Findings: The results show that service quality has a positive and significant effect on satisfaction (t = 3.075; p = 0.003). Service delivery procedures also have a positive and significant effect (t = 3.886; p = 0.002). In addition, ease of access to information has a positive and significant effect on satisfaction (t = 3.718; p = 0.000). Simultaneously, the three variables significantly influence satisfaction (F = 43.964; p = 0.000). Implications: These findings suggest that healthcare facilities can enhance user satisfaction by strengthening service quality, improving and standardizing service procedures, and ensuring information systems are clear, responsive, and easy to access supporting practical improvements in service management and information governance. Originality: This study contributes empirically by integrating service quality, service procedures, and information accessibility within a single model to explain user satisfaction in healthcare facilities, providing added value for user-oriented service improvement initiatives.